2018
DOI: 10.2147/hiv.s143929
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis and HIV coinfection: current perspectives

Abstract: Visceral leishmaniasis (VL) is caused by Leishmania donovani and Leishmania infantum. The burden of VL is concentrated in tropical and subtropical areas; however, HIV infection has spread VL over a hyperendemic area. Several outcomes are observed as a result of VL–HIV coinfection. Impacts are observed in immunopathogenesis, clinical manifestation, diagnosis, and therapeutic response. Concerning clinical manifestation, typical and unusual manifestation has been observed during active VL in HIV-infected patient,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 72 publications
0
92
0
13
Order By: Relevance
“…Respondents ranged in age from 23 years to 64 years ( Table 1). Among 29 patients, 24 were men (83%) and 5 were women (17%), reflecting the background distribution of KA-HIV patients overall [22].…”
Section: Resultsmentioning
confidence: 98%
“…Respondents ranged in age from 23 years to 64 years ( Table 1). Among 29 patients, 24 were men (83%) and 5 were women (17%), reflecting the background distribution of KA-HIV patients overall [22].…”
Section: Resultsmentioning
confidence: 98%
“…The results obtained from this systematic review showed that the prevalence rate of S. stercoralis in HIV + patients using serological method (12.4%) was higher than other methods (3.6% microscopy, 10.8% culture and 3.9% molecular assays). According to our litterateur's review, the prevalence obtained though in general serological assays for detection of pathogens can yield a low sensitivity in HIV + individuals due to the potentially reduced humoral immune response (Lindoso, Moreira, Cunha, & Queiroz, ; Segarra‐Newnham, ). This is not attributed to certain diagnostic tests being preferred for studies in different regions since all described tests have used widely in different regions (Table , Figures ).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and laboratory findings included greater weight loss in HIV mono‐infected patients. Other studies have observed a greater proportion of weight loss in VL‐HIV co‐infected compared with HIV mono‐infected patients . This divergence could be explained by the fact that in our study, the HIV group included a larger number of individuals with discontinued use of HAART compared with the VL‐HIV group.…”
Section: Discussionmentioning
confidence: 66%